Mapping average axon diameters in porcine spinal cord white matter and rat corpus callosum using d-PFG MRI - Komlosh, M.E. (2013)
Knowledge of microstructural features of nerve fascicles, such as axon diameter, is crucial for understanding normal function in the central and peripheral nervous systems as well as assessing changes due to pathologies. In this study double-pulsed field gradient (d-PFG) filtered MRI was used to map the average axon diameter (AAD) in porcine spinal cord, which was then compared to AADs measured with optical microscopy of the same specimen, as a way to further validate this MRI method. A novel 3D acquisition scheme was then used to obtain AADs in each voxel of a coronal slice of rat brain corpus callosum. AAD measurements were also acquired using optical microscopy performed on histological sections and validated using a novel MRI glass capillary array phantom.